Prevalence of ovine fasciolosis and its associated risk factors: The case of in and around Bedele Town, Bunno Bedele Zone, Oromia Region, Ethiopia - Diriba Tigire Nuqus; Dereje Abera Wako; Jiregna Dugassa Kitessa (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
Background: Ethiopia is rich in sheep and goats, accounting for 63% of the income from financial production and 23% of the cost of food. However, this immense wealth potential has not been well exploited for the support of farmers and their contribution to the economy as a whole due to various factors such as diseases. Among these, fascioliasis is one of the most economically important parasitic diseases of farm animals, especially in sheep. Objectives: To determine the prevalence and risk factors associated with ovine fasciolosis in the study area. Methods: A cross-sectional study design was conducted to determine the prevalence and risk factors associated with ovine fasciolosis in four randomly selected peasant associations in and around Bedele town by using standard fecal sedimentation techniques.  Results: Out of a total of 384 sheep faecal samples processed and examined, 85 (22.1%) were positive for fasciolosis. Risk factors such as origin, age, sex, and body condition were also assessed for the occurrence of the disease. Accordingly; Shebe (26.4%) had a higher sheep fasciolosis, followed by Yabella (22.5%), Dabena Daru (20.8%), and Bedele 02 (17.5%) with no significant differences in peasant associations (p > 0.05). The prevalence rate under different body condition scores was recorded as poor (38.6%) compared to medium (22.3%), followed by good (16.3%). Similarly, infection was found to be among female (23%) and male (21%) sex groups; but had a statistically significant association (p < 0.05). Conclusion and Recommendations: Current research suggests that fasciolosis affecting sheep was a common parasitic disease in the study area, so control strategies should be developed to reduce the spread of infection.